Patient and clinician perspectives of pelvic floor dysfunction after gynaecological cancer - Robyn Brennen; Kuan-Yin Lin; Linda Denehy; Sze-Ee Soh; Helena Frawley (Elsevier, 2022)
Purpose: To explore and compare patient and clinician experiences, knowledge and preferences in relation to screening and management of pelvic floor (PF) dysfunction in the gynaecology-oncology setting. Methods: Semi-structured interviews were conducted with women reporting PF symptoms after gynaecological cancer treatment, and gynaecology-oncology clinicians. Interviews were transcribed and thematically analysed and were conducted until data saturation was reached. Results: We interviewed 12 patients and 13 clinicians. We identified two main themes: (1) Experience with PF symptoms, screening, disclosure and management and (2) Future hope of what should happen to screen and manage PF symptoms. Differences between what participants had experienced and what they felt should happen highlighted a perceived need for improving PF screening and management. A sub-theme that reflected relevant barriers and enablers was also identified. Barriers included time pressure, being focussed on cancer treatment and not side-effects, and patients feeling unwell, emotional, and overwhelmed with the logistics of oncology appointments. Enablers included the patient-clinician relationship, and opportunities for improving management included integrating nursing and PF physiotherapy with oncology appointments. Conclusions: Gynaecological cancer survivors and clinicians perceive a need to improve screening and management for PF symptoms. While barriers and differences in perception exist, there are opportunities to improve how PF symptoms can be screened and managed in this population. Further studies exploring the feasibility of providing integrated multidisciplinary PF therapy services may be warranted.